Effects of Drilling Technology on Mini-Implant Primary Stability: A Comparison of the Mechanical Drilling and Femtosecond Laser Ablation - Zhang, Wenbin; Alghannam, Fahad; Zhu, Yingchao; Zhang, Jianfei; Wohl, Gregory R; Haugen, Harold K.; Qin, Zhipeng; Xie, Guoqiang; Fang, Qiyin; Shen, Steve Guofang (Frontiers in Physics, 2021)
Objectives: Primary stability is a fundamental prerequisite in predicting the prognosis of a mini-implant (MI) as a skeletal anchorage. This study aims to evaluate the influence of implant site preparation technology on the primary stability of MI. Methods: 108 bovine cortical bone samples were fabricated to three thicknesses (0.5mm, 1.0mm, 1.5mm). For each thickness group, the samples were divided into three subgroups: I (without site preparation), II (site preparation with a mechanical drill), and III (site preparation with femtosecond laser ablation). After MI insertion into these samples, the pull out strength of MI was measured by lateral pull out tests. Results: For the 0.5 mm thickness samples, the lateral pull out strength was 9.9±2.7N in the subgroup I, 6.7±2.1N in the subgroup II, and 15.2±2.6N in the subgroup III. For the 1.0 mm thickness samples, the lateral pull out strength was 39.3±2.5N in the subgroup I, 38.2±2.7N in the subgroup II, and 46.3±1.7N in the subgroup III. For the 1.5 mm thickness samples, the lateral pull out strength was 73.9±4.8 N in the subgroup I, 70.1±2.8N in the subgroup II, 75.0±2.2N in the subgroup III. No signs of carbonization or substantial cracking were visible in any of the bone samples. Conclusions: Site preparation with laser ablation significantly improved the lateral pull out strength over mechanical preparation and control (no site preparation) in thinner cortical bone samples (1.0 mm &0.5 mm). Such improvement in lateral pull out strength decreases as the samples become thicker and diminishes in thick (1.5mm) cortical bone samples.